Reducing the Risk of Cognitive Decline and Dementia: WHO Recommendations - Chowdhary, Neerja; Barbui, Corrado; Anstey, Kaarin J.; Kivipelto, Miia; Barbera, Mariagnese; Peters, Ruth; Zheng, Lidan; Kulmala, Jenni; Stephen, Ruth; Ferri, Cleusa P.; Joanette, Yves; Wang, Huali; et al. (Frontiers in Neurology, 2022)
With population ageing worldwide, dementia poses one of the greatest global challenges for health and social care in the 21st century. In 2019, around 55 million people were affected by dementia, with the majority living in low- and middle-income countries. Dementia leads to increased costs for governments, communities, families and individuals. Dementia is overwhelming for the family and caregivers of the person with dementia, who are the cornerstone of care and support systems throughout the world. To assist countries in addressing the global burden of dementia, the World Health Organization (WHO) developed the Global Action Plan on the Public Health Response to Dementia 2017-2025. It proposes actions to be taken by governments, civil society, and other global and regional partners across seven action areas, one of which is dementia risk reduction. This paper is based on WHO Guidelines on risk reduction of cognitive decline and dementia and presents recommendations on evidence-based, multisectoral interventions for reducing dementia risks, considerations for their implementation and policy actions. These global evidence-informed recommendations were developed by WHO, following a rigorous guideline development methodology and involved a panel of academicians and clinicians with multidisciplinary expertise and representing geographical diversity. The recommendations are considered under three broad headings: lifestyle and behavior interventions, interventions for physical health conditions and specific interventions. By supporting health and social care professionals, particularly by improving their capacity to provide gender and culturally appropriate interventions to the general population, the risk of developing dementia can be potentially reduced, or its progression delayed.